Knowledge of Hand Hygiene Practices among Healthcare workers in Neonatal and Paediatric Intensive Care Unit of a tertiary care hospital of Odisha - Choudhury, Jasashree; Mahapatra, Anuspandana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Background:The objective of this study was to assess the knowledge of hand hygiene of healthcare workers Â in the neonatal and paediatric intensive care unit in a tertiary care hospital. Methods : Study was conducted Â to assess Â the knowledge of hand hygiene for the five moments of hand hygiene of WHO. Healthcare workers Â Â were given a questionnaire during routine patient care on random basis and the data was collected. Data analysis wasÂ Â performed using SPSS software version 13. Results : A total of 50 health care workers Â were questioned during the observation period. Answers differed by role: nurses (25) and doctors (10).15 nurses have no knowledge of moments of hand hygiene and were excluded from study. Nurses Â were more likely to use soap and water compared to waterless-alcohol-based hand hygiene practices. Doctors were most likely to use alcoholic hand rub. Conclusion : Though knowledge of Â hand hygiene practice Â is high ,use of alcohol-based disinfectant was found to be very low compared to soap and water.Â Keywords: Hand hygiene, Health care, Soap and water, Alcohol hand rub.